PENGARUH PENAMBAHAN FENOL TERHADAP TEGANGAN TEMBUS AC PADA MINYAK JARAK (CASTOR OIL) SEBAGAI ALTERNATIF BAHAN ISOLASI CAIR - Handoyono, Tito Tri; Dhofir, Moch.; Hasanah, Rini Nur (Jurnal Mahasiswa TEUB, 2024)
Mineral oil-based transformer insulation has several problems, namely that it is not environmentally friendly, cannot be decomposed, cannot be renewed and its availability is decreasing. Vegetable oils are an alternative to transformer insulation, one of which is castor oil. This research aims to describe castor oil as an alternative to mineral oil for transformer insulation materials based on SPLN 49 of 1982. This research was carried out using samples of pure castor oil and castor oil with phenol additives of 1.25%, 2.5%, 3.75%. Water content testing is carried out using the heating method with the aim of reducing the water content in pure castor oil. Heating was carried out at 70ºC for 60 minutes. Breakdown voltage testing is carried out to determine thedielectric strength of castor oil. Based on the minimum requirements of SPLN 49 of 1982, the breakdown voltage is >30 kV. Permittivity and conductivity tests were also carried out on castor oil. The relative permittivity value must meet the specified requirements. The permittivity value for pure castor oil is 12.59 F/m, for castor oil with 3.75% phenol additive it is 12.77 F/m. The conductivity value of pure castor oil is 93.66 × 10^(-9)S/m, while the conductivity value of castor oil with 3.75% phenol as an additive is 3.73 × 10^(-9) S/m. Assay Pure castor oil water uses the gravimetric method and shows that the water content before heating is 3300 ppm, then heating treatment can reduce the water content by 33.06 ppm or 1%. Testing the breakdown voltage of pure castor oil which did not go through a heating process was 30.65 kV, while the breakdown voltage value of pure castor oil which was heated was 36.67 kV, this heating increased by 18.63%. The highest breakdown voltage value for castor oil with 3.75% phenol additive was 46.05 kV at room temperature, while the highest breakdown voltage value for castor oil with 3.75% phenol additive was 58.97 at a heating temperature of 70ºC for 60 minutes. Keyword: heating, Castor oil. Water content, phneol, breakdown voltage